Capital budgeting practices: evidence from Sri Lanka - Nurullah, M.; Kengatharan, L. (University of Jaffna, 2015)
Purpose – The purpose of this paper is to investigate prevailing capital budgeting practices in Sri Lankan listed companies. Design/methodology/approach – A comprehensive primary survey was conducted of 32 out of 46 chief financial officers (CFOs) of manufacturing and trading companies listed on the Colombo Stock Exchange in Sri Lanka. Garnered data were then analyzed using appropriate statistical techniques. Findings – The results revealed that net present value (NPV) was the most preferred capital budgeting method, followed closely by payback (PB) and internal rate of return (IRR). Similarly, sensitivity analysis was regarded as the dominant capital budgeting tool for incorporating risk and the widely used method for calculating cost of capital was the weighted average cost of capital. Moreover, results revealed that size of the capital budget affects the use of the capital budgeting methods (NPV, IRR and PB) and incorporating risk tool (sensitivity analysis and simulation). Further, results revealed that CFOs had higher educational qualification were preferred to use sophisticated capital budgeting practices dominantly NPV, IRR and incorporating risk tool of sensitivity analysis although they were found to be reluctant in use of accounting rate of return. In a similar vein CFOs with higher experience were preferred using IRR and sensitivity analysis. Originality/value – This study contributed to academics, practitioners, policy makers and stakeholders of the company. Moreover, this research has proffered a more reliable and comprehensive analysis of capital budgeting practices in Sri Lankan listed manufacturing and trading firms. Since Sri Lanka is an unexplored country on capital budgeting practices, this research was originally contributed to the extant literature per se.
Keywords: Sensitivity analysis; NPV; Risk; Financial management; Capital budgeting; IRR; WACC